2021
DOI: 10.1177/02676583211030604
|View full text |Cite
|
Sign up to set email alerts
|

Spoken word recognition in a second language: The importance of phonetic details

Abstract: Spoken word recognition depends on variations in fine-grained phonetics as listeners decode speech. However, many models of second language (L2) speech perception focus on units such as isolated syllables, and not on words. In two eye-tracking experiments, we investigated how fine-grained phonetic details (i.e. duration of nasalization on contrastive and coarticulatory nasalized vowels in Canadian French) influenced spoken word recognition in an L2, as compared to a group of native (L1) listeners. Results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This possibility is supported by work showing that native and nonnative listeners rely on different strategies—namely, lexical knowledge versus acoustic cues—during word segmentation (Mattys et al, 2010). It has also been found that native speakers show gradient integration of phonetic information (as measured by eye-tracking) during word recognition, whereas nonnative speakers show a categorical pattern (Desmeules-Trudel, 2018). An additional possibility is that greater sensitivity to native speech sounds does promote better nonnative perception, but that this relationship emerges later in life.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported by work showing that native and nonnative listeners rely on different strategies—namely, lexical knowledge versus acoustic cues—during word segmentation (Mattys et al, 2010). It has also been found that native speakers show gradient integration of phonetic information (as measured by eye-tracking) during word recognition, whereas nonnative speakers show a categorical pattern (Desmeules-Trudel, 2018). An additional possibility is that greater sensitivity to native speech sounds does promote better nonnative perception, but that this relationship emerges later in life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mattys et al (2010) showed that in the presence of cognitive load (speech perception accompanied by a distracting visual search task), native and non-native listeners' word segmentation relied on a different source of information; non-native listeners tend to make less use of lexical knowledge and more use of acoustic cues compared to native listeners. Similarly, Desmeules-Trudel (2018) reported that French-speaking L2 learners of Canadian English (even those with early exposure to the L2) patterned differently from L1 Canadian English listeners in integrating fine-grained acoustic information (nasalization duration of nasal vowels) for spoken word recognition. L2 learners were not gradient (but rather categorical) in word recognition as acoustic information of nasalization duration varied, whereas L1 listeners responded to conflicting acoustic information in a gradient manner.…”
Section: Implication Of Categorical Judgment On L2 Learningmentioning
confidence: 95%
“…An increasing number of studies on L2 phonetics, indeed, have suggested that learners can be sensitive to the phonetic detail in L2 and eventually learn to produce it, enriching the model architecture of SLM(-r) and PAM-L2 in terms of the role of the non-contrastive phonetic detail in L2 acquisition (see Flege, 2003, or Best & Tyler, 2007, for a review). In terms of L2 perception of non-contrastive cues, for example, evidence from psycholinguistic studies indicates that L2 listeners utilize fine-grained phonetic details (i.e., vowel nasalization duration) when perceiving L2 sounds or words (e.g., Desmeules-Trudel & Zamuner, 2021). In terms of production, a seminal study by Flege (1987) showed that both native English learners of French and native French learners of English were sensitive to the phonetic detail of VOT in each target language, producing VOTs that were different from those in their native languages but closer to those of each target language.…”
Section: Introductionmentioning
confidence: 99%